2014
DOI: 10.1097/med.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Human β-cell regeneration

Abstract: Purpose of review Therapies that increase functional β-cell mass may be the best long-term treatment for diabetes. Significant resources are devoted toward this goal, and progress is occurring at a rapid pace. Here, we summarize recent advances relevant to human β-cell regeneration. Recent findings New β-cells arise from proliferation of pre-existing β-cells or transdifferentiation from other cell types. In addition, dedifferentiated β-cells may populate islets in diabetes, possibly representing a pool of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 95 publications
(101 reference statements)
1
6
0
Order By: Relevance
“…The findings of this study were in line with Jurczyk et al [26] who found that the histological studies on human tissue in adult who exposed to any stress factors showed insulin-expressing cells in ducts, isolated β-cells in the pancreatic parenchyma, and small islet clusters. PRP had consistently shown to potentiate stem cell proliferation, migration, and differentiation (Masoudi et al [33]).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The findings of this study were in line with Jurczyk et al [26] who found that the histological studies on human tissue in adult who exposed to any stress factors showed insulin-expressing cells in ducts, isolated β-cells in the pancreatic parenchyma, and small islet clusters. PRP had consistently shown to potentiate stem cell proliferation, migration, and differentiation (Masoudi et al [33]).…”
Section: Discussionsupporting
confidence: 81%
“…Another one of PRP GFs; insulin growth factor, localized to the focal areas of regeneration and may play an important role in pancreatic regeneration by autocrine mechanisms through stimulation of DNA synthesis [35]. This could take place by using replication of already differentiated β-cells (β-cell plasticity) or neogenesis from putative islet stem cells in the ductal or acinar epithelium [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the size of the islets and budding of new islets by R-Tf-D-LP4 peptide treatment of STZ/HFD-32 fed mice raised the question as to the source of these β-cells. The possibility that they might regenerate is controversial and is currently a subject of debate [62,63]. One leading theory suggests that the formation of new islets is caused by the differentiation of progenitor or stem cells to β-cells [64], while an opposing theory suggests that differentiated cells in the pancreas or liver undergo a process of trans-differentiation by which cells de-differentiate and then re-differentiate to β-cells [63,65].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that they might regenerate is controversial and is currently a subject of debate [62,63]. One leading theory suggests that the formation of new islets is caused by the differentiation of progenitor or stem cells to β-cells [64], while an opposing theory suggests that differentiated cells in the pancreas or liver undergo a process of trans-differentiation by which cells de-differentiate and then re-differentiate to β-cells [63,65]. Another possible explanation is proliferation of β-cells, although the total β-cell proliferation rate was observed to be low in both mice and humans, as only a fraction of these cells proliferate [66].…”
Section: Discussionmentioning
confidence: 99%